2015
DOI: 10.1002/stem.2058
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Satellite Cell Protein Teneurin-4 Regulates Differentiation During Muscle Regeneration

Abstract: Satellite cells are maintained in an undifferentiated quiescent state, but during muscle regeneration they acquire an activated stage, and initiate to proliferate and differentiate as myoblasts. The transmembrane protein teneurin‐4 (Ten‐4) is specifically expressed in the quiescent satellite cells; however, its cellular and molecular functions remain unknown. We therefore aimed to elucidate the function of Ten‐4 in muscle satellite cells. In the tibialis anterior (TA) muscle of Ten‐4‐deficient mice, the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…They include an over-representation of genes in the TNFα pathway via NFKβ signaling, Il6-Jak-Stat3 signaling, and the apical surface processes, and an under-representation of MYC and E2F targets, and genes associated with the G2 M checkpoint and oxidative phosphorylation. Some markers such as Calcitonin receptor ( Calcr ), Teneurin4 ( Tenm4 ), and stress pathways identified previously were also present in our analysis [ 11 , 41 , 55 ] (Additional file 6 : Table S2). However, we also report that virtually all datasets contained genes that would be expected to be present during activation or cell cycle entry, such as members of the Fos and Jun family previously identified as immediate early stress response genes [ 56 ].…”
Section: Discussionmentioning
confidence: 59%
“…They include an over-representation of genes in the TNFα pathway via NFKβ signaling, Il6-Jak-Stat3 signaling, and the apical surface processes, and an under-representation of MYC and E2F targets, and genes associated with the G2 M checkpoint and oxidative phosphorylation. Some markers such as Calcitonin receptor ( Calcr ), Teneurin4 ( Tenm4 ), and stress pathways identified previously were also present in our analysis [ 11 , 41 , 55 ] (Additional file 6 : Table S2). However, we also report that virtually all datasets contained genes that would be expected to be present during activation or cell cycle entry, such as members of the Fos and Jun family previously identified as immediate early stress response genes [ 56 ].…”
Section: Discussionmentioning
confidence: 59%
“…This finding is aligned with our results showing that ectomesenchymal cells from dental papilla exhibited Ten-2 immunoreactivity, prior to odontoblast differentiation. Previous studies showed that teneurins are involved with nervous and muscle tissue regeneration processes [ 38 , 39 ]. Additional data from our laboratory demonstrated Ten-2 presence in astrocytes after mechanical brain lesion, supporting its role during tissue regeneration (submitted manuscript).…”
Section: Discussionmentioning
confidence: 99%
“…They include an over-representation of genes in the TNFa pathway via NFKb signaling, Il6-Jak-Stat3 signaling, and the apical surface processes, and an under-representation of MYC and E2F targets, and genes associated with the G2M checkpoint and oxidative phosphorylation. Some markers such as Calcitonin receptor (Calcr) , Teneurin4 ( Tenm4 ), and stress pathways identified previously were also present in our analysis [51][52][11]. However, we also report that virtually all datasets contained genes that would be expected to be present during activation or cell cycle entry, such as members of the Fos and Jun family previously identified as immediate early stress response genes [53].…”
Section: Discussionmentioning
confidence: 53%